Earthquake Relocation in Northern Bali Island in 2015-2017 using Double Difference Method (DD) - Diaz, Nandaru; Suarbawa, Komang Ngurah; Mursitantyo, Adityo (BULETIN FISIKA; Vol 19 No 2 (2018): BULETIN FISIKA, 2018)
A research about earthquake relocation in Northern Bali Island in 2015 – 2017 using the Double Difference (DD) method has been carried out. Earthquake relocation is important to get some informations about earthquake locations with high accuracy, fault zone identification, earthquake distribution and seismic analysis. The results of the relocation indicated that there was a displacement of the location of earthquake that formed moving closer to the earthquake source namely a fault. Relocation using HypoDD program gave high accurate result indicated by the RMS residual time value close to zero e.g. 0,000 - 0.01 which mean the results of calculations and observations are closed to the real value.